2019
DOI: 10.33692/avrasyad.543857
|View full text |Cite
|
Sign up to set email alerts
|

Bölgesel Kalkinma Poli̇ti̇kasi Araci Olarak Kamu Yatirimlari Ve Teşvi̇kler: Türki̇ye’de Düzey 2 Bölgeleri̇ Üzeri̇ne Bi̇r Etki̇nli̇k Anali̇zi̇

Abstract: ÖZ 1950'lerle birlikte başlayan ve giderek artan bölgesel eşitsizlikler halen ekonomilerin çözmek zorunda kaldığı ciddi sorunların başında gelmektedir. Bu sorunla mücadele eden ekonomilerin kullandığı temel politika araçlarından biri de kamu eliyle yürütülen teşvik programlarıdır. Dünya genelinde ülke ekonomilerinin giderek daha liberalleşmesine karşın kalkınma politikalarında kamusal teşviklerden vazgeçmemesi bir dilemma gibi görülebilir. Finansal liberalizasyonu destekleyen ve aynı zamanda kalkınma politikal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Yavan (2011), one of the leading studies in Turkish literature, found that the investment incentives had a positive impact on regional economic growth. There are also regional studies examining the effects of investment incentives for Turkey (Karaalp, 2014;Selim et al, 2014;Demirtaş and Aksel, 2018;Baykul et al, 2019). Gerni et al (2015), Sevinç et al (2016) and Gömleksiz et al (2017) determined that the investment incentives had positive impacts on economic growth in 26 development regions of Turkey for different years.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yavan (2011), one of the leading studies in Turkish literature, found that the investment incentives had a positive impact on regional economic growth. There are also regional studies examining the effects of investment incentives for Turkey (Karaalp, 2014;Selim et al, 2014;Demirtaş and Aksel, 2018;Baykul et al, 2019). Gerni et al (2015), Sevinç et al (2016) and Gömleksiz et al (2017) determined that the investment incentives had positive impacts on economic growth in 26 development regions of Turkey for different years.…”
Section: Literature Reviewmentioning
confidence: 99%